PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA SUKU DINAS SUMBER DAYA AIR KOTA ADMINISTRASI JAKARTA BARAT - Nyoman Devi Arysta, Ni; Rizka Akbar, Irfan (Journal of Research and Publication Innovation, 2023)
The purpose of this study was to determine the effect of organizational culture on performance, work disipline onperformance and organizational culture and work discipline on employee performance at the West Jakarta Administrative City Water Resources Office. The method used is quantitative. The sampling technique used saturated sampling and obtained a sample of 83 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are that organizational culture has a significant effect on employee performance this is evidenced by the regression equation Y = 12,404 + 0,682X1 with a coefficient of determination of 46.5% and the hypothesis test is obtained t count > t table or (8.395 > 1.990). Work discipline has a significant effect on employee performance this is evidenced by the regression equation Y = 12,275 + 0,679X2 with a determination coefficient value of 53.7% and hypothesis testing obtained t count > t table or (9.700 > 1.990). Organizational culture and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 6.665 + 0.366X1 + 0.466X2. The coefficient of determination is 61.9% while the remaining 38.1% is influenced by other factors. Hypothesis testing obtained F count > F table or (64.874 > 2.720). This job organization cilture and work disipline together have a positive and significant impact on employee performance the West Jakarta Administrative City Water Resources Office.